The Role of Brand Awareness in Mediating the Influence of Beauty Vlogger Credibility on Axis-Y Product Buying Interest - Sari, Luh Kartika Purnama; Oktora P, I Gede nandya; Kusumadewi, Ni Made Wulandari; Suwandana, I Gusti Made (Al-Makki Publisher, 2025)
This study aims to examine the role of brand awareness in mediating the influence of beauty vlogger credibility on buying interest in Axis-Y skincare products. The phenomenon of increasing use of social media, especially YouTube, has made beauty vloggers one of the main sources of information in the beauty field. One of them is Suhay Salim, who is known to have a large following and product review content. However, the low interest in buying Axis-Y products even though it has been reviewed shows that there are other factors that influence, one of which is brand awareness. This study uses a quantitative method with path analysis and Sobel test techniques. The research sample of 100 respondents who met the criteria had watched Suhay Salim's video about Axis-Y but had never bought the product. The results of the study show that the credibility of beauty vloggers has a positive and significant effect on brand awareness and buying interest. In addition, brand awareness has been proven to mediate the indirect influence of beauty vlogger credibility on buying interest. These findings show the importance of the role of beauty vloggers and brand awareness in increasing consumer buying interest.